Bandwidth modulation and centre wavelength shift of a single FBG for simultaneous water level and temperature sensing. (15th October 2020) - Vorathin, E.; Hafizi, Z.M.
Highlights: A hydrostatic level transducer for simultaneous measurement of water level and temperature is proposed. Bandwidth and centre wavelength change measurement technique is used. Water level variations change the bandwidth and centre wavelength of the spectrum. Temperature variations only change the centre wavelength of the spectrum. Matrix equation is used to predict the water level and temperature measurement. Abstract: A diaphragm-based hydrostatic level transducer with the use of a single Fibre Bragg grating (FBG) is presented for simultaneous measurement of water level and temperature. In order to distinguish the mismatch between water level and temperature sensitivity, a bandwidth modulation and centre wavelength shift measurement technique was introduced. The change in bandwidth is sensitive towards water level variations with a sensitivity of 0.0015 nm/cm. Meanwhile, the change of centre wavelength is sensitive towards water level and temperature variations, with sensitivities of 0.0008 nm/cm and 0.0365 nm/°C, respectively. By expressing the obtained sensitivities in a matrix equation approach, simultaneous water level and temperature measurement can be predicted accurately.